Potensi brown anchovy dalam remineralisasi gigi: tinjauan terhadap kekerasan dan mikroporositas email - Elline; Shafira Prana, Indira; Ratnasari, Dina; Elsa Prahasti, Anastasia; Ariwibowo, Taufiq; Pratiwi, Deviyanti (Jurnal Kedokteran Gigi Terpadu, 2025)
The process of dental demineralization can lead to the dissolution of minerals in hydroxyapatite crystals, increasing interprismatic spaces and decreasing enamel hardness. This demineralization can be inhibited through remineralization, supported by natural ingredients such as brown anchovy, which have potential as remineralizing agents. The remineralization process can be observed through changes in enamel microhardness and microporosity. Objectives: This article aims to provide information about the potential of brown anchovy and its effects on enamel microhardness and microporosity. Conclusion: There is potential of brown anchovy and its benefit in teeth remineralization.